Digital therapeutics approach for young children with myopia using SAT-001 (DAYS): study protocol for a randomized controlled trial - Hae Jung Paik; Byung Joo Lee; Dong Hui Lim; So Young Han; Eun Hye Jung; Hyun Jin Shin; Hyun Kyung Kim; Ungsoo Samuel Kim; Won Jae Kim; Hee Young Choi; Jihae Park; Soolienah Rhiu; et al. (Trials)
Abstract Background Myopia is a prevailing refractive disorder and rapidly increases the risk of vision-threatening conditions. Earlier intervention is crucial to suppress myopia progression; however, the pharmacological and non-pharmacological therapies currently available have limitations. SAT-001 is a novel digital therapeutic software developed for myopia control and is designed to overcome the limitations of existing therapies. The present study aims to evaluate the efficacy and safety of the software as a medical device, SAT-001, for the inhibition of myopia progression and treatment in pediatric patients with myopia. Methods This clinical trial is a two-arm, prospective, randomized, open-label study with a duration of approximately 25 months, comprising a maximum of 52 weeks of participant participation. We will enroll 110 pediatric patients with myopia aged 5 to < 9 years, each with a spherical equivalent of − 0.75 D to − 5.75 D in each eye. Eligible participants will be randomly assigned in a 1:1 ratio to either the study group using SAT-001 with single-vision spectacles or the control group using single-vision spectacles alone. The change in the spherical equivalent refractive error (SER) at 48 weeks from baseline serves as the primary endpoint. The change in SER at 24 weeks and axial length at every 12 weeks from baseline will be the secondary endpoints. Each change will be assessed depending on the myopic severity. Treatment emergent adverse events will be evaluated for the safety analysis. Discussion This randomized controlled trial aims to confirm the efficacy and safety of SAT-001 in slowing pediatric myopia progression. The findings of this study could establish SAT-001 as an easily accessible, convenient, and non-invasive treatment option with minimal side effects, offering long-term myopia control from an early stage. Further research is needed to validate the effectiveness of SAT-001 for moderate to high myopia and concurrent conditions like astigmatism and to improve user engagement, diversify the program, and integrate with hospital-based treatments. Trial registration ClinicalTrials.gov: NCT06344572 ; date of registration: April 12, 2024 (retrospectively registered).